Efecto del movimiento sísmico vertical durante la construcción de puentes - Álvarez Mosqueda, Otilio (Universidad Michoacana de San Nicolás de Hidlgo, 2012)
The features of the vertical component and the effect caused by the vertical acceleration to the bridges, have been studied by several researchers (Broekhuizen, 1996; Papazoglou and Elnashai, 1996; Collier and Elnashai, 2001, Button et al., 2002); however, there is a lack of study during the stages of construction of such structures.The interest and the importance of studying the effect of the vertical component for building bridges originates in different strength and stiffness characteristics that have the means and long bridges during the construction phases, which differ markedly from those of the bridges completed . Besides construction times favor the occurrence of earthquakes of moderate and / or high magnitudes, which is unfavorable for such structures during construction. The collapse happened in 2004 during the construction of the bridge pushed "San Cristobal", on the road that connects the cities of Tuxtla Gutierrez and San Cristobal de Las Casas, Chiapas, was additional motivation for the study of the vertical component earthquakes during the construction of large bridges. Since 1973, when Newmark et al. published the results of a study where ratios obtained maximum ground accelerations of the vertical component between the horizontal (V / H) of 33 US seismic records it has been considered as the vertical component to the horizontal 2/3 reasons of design. However, subsequent studies have concluded that such value is inappropriate, especially for near-field earthquakes and high magnitudes cases where the ratio V / H exceeds the unit are presented.

Las características de la componente vertical y el efecto que ocasiona la aceleración vertical a los puentes, han sido estudiadas por varios investigadores (Broekhuizen, 1996; Papazoglou and Elnashai, 1996; Collier and Elnashai, 2001; Button et al., 2002); sin embargo, existe una carencia del estudio durante las etapas de construcción de este tipo de estructuras. El interés y la importancia de estudiar el efecto de la componente vertical durante la construcción de puentes se origina en las distintas características de resistencia y rigidez que tienen los puentes medios y largos durante las fases constructivas, y que difieren notablemente de las de los puentes terminados. Además los tiempos de construcción favorecen la ocurrencia de sismos de magnitudes moderadas y/o altas, lo cual resulta desfavorable para este tipo de estructuras durante su construcción. El derrumbe que ocurrió en el año 2004 durante la construcción del puente empujado “San Cristóbal”, en la carretera que conecta las ciudades de Tuxtla Gutiérrez y San Cristóbal de Las Casas, en Chiapas, fue motivación adicional para el estudio de la componente vertical de los sismos durante la construcción de puentes grandes. Desde 1973, cuando Newmark et al. Publicaron los resultados de un estudio donde obtuvieron los cocientes de las aceleraciones máximas del terreno de la componente vertical entre la horizontal (V/H) de 33 registros sísmicos de EEUU, se ha considerado la componente vertical como 2/3 de la horizontal para motivos de diseño. Sin embargo, estudios posteriores han concluido que tal valor resulta inadecuado, sobre todo para sismos de campo cercano y magnitudes altas donde se presentan casos en los que la relación V/H sobrepasa la unidad.
Facultad de Ingeniería Civil. Maestría en Ingeniería en el Área de Estructuras
Keywords: info:eu-repo/classification/cti/7; FIC-M-2012-0076; Movimiento sísmico vertical; Construcción; Puentes; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4040